Small Creature, High Pressure: Compartment Syndrome as an Unusual Complication of Dengue Virus Infection: A Case Series - Ayu Islami, Sonia; Suseno Bayuadi, Imam Suseno; Sukresno, Bayu; Bondan, Bondan; Ashmi Puspitasari, Ika; Ika Faramita, Nanditya; Kusuma Anjelin, Isabella (Fakultas Kedokteran Universitas Brawijaya, 2025)
Dengue Hemorrhagic Fever (DHF) is a severe form of dengue infection characterized by plasma leakage, hemorrhagic manifestations, and organ involvement. Compartment syndrome, although rare in DHF, presents a significant challenge due to its limb-threatening nature and the delicate balance required in fluid management. We report two cases of DHF complicated by compartment syndrome occurring within a month in a single hospital. The first case involves a 41-year-old male referred with a 5-day history of fluctuating fever, who subsequently developed severe right leg pain and swelling. Despite initial management with IV fluids, antiemetics, and gastroprotective agents, the patient’s condition worsened, leading to the diagnosis of compartment syndrome. Emergency fasciotomy revealed significant muscle necrosis and bleeding. Despite aggressive resuscitation, the patient progressed to refractory shock and passed away. The second case followed a similar clinical course, highlighting the rapid progression from stable DHF to severe complications and the critical role of prompt surgical intervention. These cases illustrate the severe complications associated with DHF, particularly when complicated by conditions like compartment syndrome. Early recognition and a multidisciplinary approach are crucial. Managing such cases involves navigating the delicate balance of fluid resuscitation to prevent shock while avoiding worsening compartment pressures. DHF with compartment syndrome requires vigilant monitoring, early surgical intervention, and coordinated care among specialties. These cases highlight the necessity for further research into the interaction between DHF and compartment syndrome to guide more effective management strategies.